2023
DOI: 10.1038/s41598-023-33885-7
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur supplementation enhances nitric oxide efficacy in reversal of chromium-inhibited Calvin cycle enzymes, photosynthetic activity, and carbohydrate metabolism in wheat

Abstract: The present study demonstrated that exogenously-sourced nitric oxide (as SNP, sodium nitroprusside; NO donor) and sulfur (S) protected photosynthesis against chromium (Cr) stress in wheat (Triticumaestivum L. cv. HD 2851). Plants grown with 100 µM Cr exhibited higher reactive oxygen species (ROS) production, resulting in photosynthetic damage. The individual application of 50 µM NO increased carbohydrate metabolism as well as photosynthetic parameters, antioxidant system with higher transcriptional gene levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 66 publications
(102 reference statements)
0
0
0
Order By: Relevance
“…Glutathione (GSH) generated in plants is a low-molecular-weight antioxidant that can enhance important functions, such as reducing intracellular peroxides, scavenging free radicals, and chelating heavy metals. Fatma et al [20] found that the toxicity of Cr to the photosynthesis of wheat can be mitigated by the exogenous addition of S and NO, essentially by increasing the level of GSH, and thus mitigating the toxic effects of Cr on photosynthesis and the activity of Calvin cycle enzymes in leaves. Whether the effect of Cr (VI) on the photosynthesis of Coix lacryma-jobi L. is mitigated by regulating the GSH content in leaves under the condition of domestic sewage added needs to be studied in depth.…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione (GSH) generated in plants is a low-molecular-weight antioxidant that can enhance important functions, such as reducing intracellular peroxides, scavenging free radicals, and chelating heavy metals. Fatma et al [20] found that the toxicity of Cr to the photosynthesis of wheat can be mitigated by the exogenous addition of S and NO, essentially by increasing the level of GSH, and thus mitigating the toxic effects of Cr on photosynthesis and the activity of Calvin cycle enzymes in leaves. Whether the effect of Cr (VI) on the photosynthesis of Coix lacryma-jobi L. is mitigated by regulating the GSH content in leaves under the condition of domestic sewage added needs to be studied in depth.…”
Section: Introductionmentioning
confidence: 99%